Las relaciones entre autonomía colectiva y gobierno en Uruguay: crónica con final abierto - Barretto, Hugo (2012)
Relations between collective autonomy and government in Uruguay: chronic with open ending The present article, after making a brief recount of the model of Uruguayan collective labor relations, analyzes the foundation and impact of heteronomous regulation on the protection of trade union freedom and collective bargaining released in the context of transformation model during periods from 2005 to 2009 and so far until 2012, with the purpose of determining whether the same meant a profound and definitive break of the pre-existing model or rather it emphasizes some of its elements without disturbing the nature